THE CIREMAI MOUNTAIN CURRICULUM IN A BRAIN-BASED LEARNING E-MODULE: AN EFFORT TO ENHANCE STUDENTS"™ MATHEMATICAL CREATIVE THINKING ABILITY - Adiastuty, Nuranita; Aeni, Dilla Dzahrotul; Syafari, Rahayu (Jurnal Pendidikan Matematika dan IPA, 2025)
This study aims to develop a Brain-Based Learning (BBL) e-module based on the Gunung Ciremai Curriculum to enhance junior high school students' mathematical creative thinking on plane figures. Using the ADDIE Research and Development model, the study involved 30 seventh-grade students from class VII C at SMP Negeri 1 Kramatmulya. Instruments included validation and practicality questionnaires, as well as pre- and post-tests. The e-module was rated highly valid by material experts (88.54%) and media experts (81.94%), and valid by cultural experts (72.5%). Practicality scores were very high from both teachers (95.31%) and students (84.93%). An average N-Gain of 0.6 indicated a moderate improvement in creative thinking. These results show that the e-module is valid, practical, and effective in fostering mathematical creative thinking by integrating local cultural elements, particularly Kuningan batik, into learning. This study contributes by developing and validating a Brain-Based Learning (BBL) E-Module integrated with ethnomathematics of the Gunung Ciremai Curriculum, which is proven practical and effective in enhancing students"™ mathematical creative thinking skills.